Biocomposite Suture Anchors Remain Visible Two Years After Rotator Cuff Repair. Issue 6 (June 2019) - Sgroi, Mirco; Friesz, Theresa; Schocke, Michael; Reichel, Heiko; Kappe, Thomas
Abstract: Background: Biocomposite suture anchors containing osteoconductive materials have gained popularity in rotator cuff repairs. However, little is known about the influence of the addition of osteoconductive materials on implant resorption, bone reaction, tendon healing, and clinical outcomes scores. Questions/purposes: (1) What percentage of suture anchors were not completely resorbed 2 years after implantation? (2) What are the diameters of the bone bed in relation to the implant? (3) Is tendon integrity correlated with bone tunnel diameter? (4) Is there an association between tunnel widening, periimplant fluid film grade, biodegradation grade, and retear with clinical outcomes scores, such as the Western Ontario Rotator Cuff Index (WORC) and the Oxford Shoulder Score (OSS)? Methods: Thirty-six patients were enrolled from August 2012 to January 2014. The following inclusion criteria were applied: (1) reparable full-thickness supraspinatus tendon tears, (2) double-row suture bridge techniques applied for supraspinatus repair, (3) use of biocomposites suture anchor implants composed of poly L-lactic acid (PLLA) and β-tricalcium phosphate (TCP) exclusively, and (4) a minimum of 2 years followup. Four patients met the exclusion criteria, and seven of 36 patients (19%) were lost to followup. Thereby, 25 patients (84 implants) were included in this retrospective study. To answer the study's questions, the following methods were applied: (1) The resorption of the implants and periimplant fluid film were assessed on MRI using a four-stage scale system, (2) bone bed diameter was measured on MRI at three different points on the longitudinal central axis of each anchor, (3) tendon integrity was evaluated on MRI according to the Sugaya classification and correlated to bone tunnel diameter, and (4) assessed tunnel diameters, periimplant fluid film grade, biodegradation grade, and tendon condition were related to clinical outcomes scores at the time of followup (2.3 ± 0.3 years). The intraobserver reliability was 0.981 (p < 0.001) and interobserver reliability was 0.895 (p < 0.001). Results: At 2.3 ± 0.3 years, most analyzed suture anchors (76 of 84 [90%]) were, with varying degrees of degradation, still visible. Bone tunnels showed minor widening (0.4 ± 1.4 mm) at the base, but osseous ingrowth was detected as narrowing at the middle (0.1 ± 1.1 mm) and at the apex (1.4 ± 1.7 mm) of the implants. Patients with retears (Sugaya Grades 4-5) had narrower tunnels (3.6 ± 1.8 mm) than patients without retears (Sugaya Grades 1-3; 4.4 ± 1.6 mm; mean difference, 0.782 [95% confidence interval CI: 0.009–1.6]; p = 0.050). WORC and Oxford scores were not associated with the tunnel widening amount, fluid film grade, biodegradation grade, or tendon retear. Conclusions: In light of the results of the present study, surgeons should consider in their daily practice that the resorption process of these implants may be slower than assumed so far, but no association with severe implant-related complications has been found in the short term. Future studies should focus on the evaluation of the effects of osteoconductive materials on resorption, tendon healing, and clinical outcomes in the long term and on the integration process in different rotator cuff reconstruction techniques. Level of Evidence: Level IV, therapeutic study.